Case report: Endovascular intervention of internal carotid artery pseudoaneurysm secondary to nasopharyngeal carcinoma radiotherapy - Li, Chao; Lu, Jiachao; Luo, Yu; Feng, Daqin (Frontiers in Surgery, 2023)
Background: Internal carotid artery pseudoaneurysm (PSA) is a serious complication after radiotherapy for nasopharyngeal carcinoma, and once it ruptures and bleeds, it will seriously affect the patient's survival and prognosis. However, because its incidence is not high, many medical institutions lack experience in managing this type of emergency. Case information: In this case report, we described two cases suffered ruptured internal carotid artery PSA after radiotherapy for nasopharyngeal carcinoma, including their history, diagnosis, and treatment. Both cases underwent emergency endovascular interventions, the first with long-term healing after embolization of the pseudoaneurysm, and the second with recurrence after embolization, which was eventually stopped only by embolization of the aneurysm-carrying artery. Ultimately, both cases received more timely and effective assistance. Conclusion: This case report details the diagnosis and treatment course of internal carotid artery PSA after radiotherapy for nasopharyngeal carcinoma, which enhances the understanding of treating this emergency. Besides, our innovation in endovascular intervention will provide valuable experience in treating similar diseases.